ASSOCIATION OF AGE AND FOUR SCORE WITH ICU LENGTH OF STAY IN POST-CRANIOTOMY PATIENTS AT SAKINAH HOSPITAL MOJOKERTO - Rudi Hariyono; Ika Ainur Rofi’ah (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
This study aimed to analyze the association factors between age, FOUR Score, and ICU  length  of  stay  among  post-craniotomy  patients  treated  at  Sakinah  Hospital.  A cross-sectional study was conducted from 01 October to 12 December 2025 involving adult  post-craniotomy  patients  admitted  consecutively  to  the  ICU.  Eligible participants  were  ≥18  years  old,  intubated  postoperatively,  and  had  a  completed FOUR  Score  assessment.  Fisher’s  Exact  Test  and  relative  risk  (RR)  with  95% confidence intervals (CI) were applied to examine associations between age, FOUR Score, and ICU LOS. A significance level of p < 0.05 was used. 29 patients, 58.6% were aged ≥53 years and 62.1% experienced prolonged ICU stay. A FOUR Score ≤10 was observed in 58.6% of the cohort. Lower FOUR Scores were strongly associated with prolonged ICU stay (p < 0.000; RR = 9.7; 95% CI: 1.4–63.8). Older age also demonstrated a significant association with extended LOS (p = 0.018; RR = 2.47; 95% CI: 1–7.7). Both advanced age and lower FOUR Scores were significant  associated with prolonged ICU stay among post-craniotomy patients. These findings underscore the  utility  of  integrating  neurological  scoring  with  demographic  risk  profiling  to support early prognostication and guide resource allocation in neurosurgical critical care.